Outcomes of endoscopic submucosal dissection for early oesophageal squamous cell neoplasia at a Western centre. Issue 8 (1st October 2019) - Lorenzo, Diane; Barret, Maximilien; Leblanc, Sarah; Terris, Benoit; Beuvon, Frédéric; Coriat, Romain; Chaussade, Stanislas; Prat, Frédéric
Abstract : Background and aims: Endoscopic submucosal dissection is the reference treatment for early oesophageal squamous cell carcinoma. However, data from Western centres are scarce. Methods: We conducted a retrospective study from a prospectively collected database at a tertiary care centre in France. All consecutive patients undergoing endoscopic submucosal dissection for oesophageal squamous cell carcinoma were included. The main outcome was the curative resection rate. Secondary outcomes were en‐bloc resection rates, histologically complete resection rates, morbidity, recurrence‐free and overall survival. Results: Fifty‐six cases of oesophageal squamous cell carcinoma (49 patients; mean age 61.5 ± 10 years; 36 men) were included. En‐bloc, histologically complete and curative resection rates were 98%, 86% and 71%, respectively. Fifteen (30%) patients received an additional treatment after endoscopic submucosal dissection, nine treated by chemoradiotherapy, four by surgery and two by further endoscopic submucosal dissection. Within a mean follow‐up of 21 ± 15 months, recurrences occurred in 14 (29%) patients (four local, eight metachronous and three distant recurrences). Eight patients died during follow‐up, of which two (4%) patients died from oesophageal squamous cell carcinoma. Factors significantly associated with mortality in this series were: moderate or poor differentiation of oesophageal squamous cell carcinoma ( p = 0.02) and recurrence of oesophageal squamous cell carcinoma ( p = 0.028). Conclusion: Moderately or poorly differentiated cancer is a major prognostic factor and should probably be taken into account when indicating an additional treatment after endoscopic submucosal dissection. Close endoscopic follow‐up is essential considering the high recurrence rate.